Pengaruh CSR, Technology dan CEO Education terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Fawwaz, Emil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine the influence of CSR, Technology and CEO Education on company profitability. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2017 - 2022. The independent variables in this research are CSR, Technology, CEO Education and the dependent variable is company profitability. The total research sample was 26 manufacturing companies using purposive sampling. The empirical results of this research use the eviews 9 program with panel data regression. Based on panel data regression results, it shows that Technology has an influence on company profitability, while CSR and CEO Education have no influence on company profitability. . It is hoped that the results of this research can be a reference for companies and investors to increase company profitability.